Measurement and sources of technical efficiency of land tenure contracts in Ethiopia - Ahmed, M.M.; Gebremedhin, Berhanu; Benin, Samuel; Ehui, Simeon K. (Cambridge University Press, 2002)
The degree to which prevailing land tenure arrangements constrain agricultural productivity, and the sources of inefficiency associated with land tenure systems in sub-Saharan Africa are unresolved. Using a stochastic frontier production function, this paper examines the economic efficiency and the determinants of inefficiency of alternative land tenure arrangements in Ethiopia. The results show that sharecropping and borrowing are less technically efficient than owner-cultivation or fixed rentals due to restrictions imposed on them by landowners and the interactions of the land market with other imperfect and absent input markets. Thus, a policy to facilitate more efficient transactions of land between farmers and functioning of input markets are expected to reduce inefficiencies associated with these tenure systems.